Perancangan Buku Pop Up Ilustrasi Bergambar sebagai Media Pengenalan Seni Pertunjukan di Jawa Timur untuk Anak Usia Dini - Alfonsin Celly Stella; Sultan Arif Rahmadianto; Didit Prasetyo Nugroho (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2020)
Nowadays cultural inheritance among youth is very small, therefore citizen’s awareness to save Indonesian heritage is a priority especially cultural introduction for early childhood. Cultural introduction that was raised in this prototype is about cultural arts in East Java, among others: Jaranan Senterewe, Karapan Sapi, Ludruk, Reog Ponorogo, Remo Dance, Gandrung Dance, Topeng Malang Dance, and Tayuban Dance. Cultural introduction can be done trough pop up books. Besides cultural introduction, this prototype contained alphabets introduction, size of objects (big-small), and number of objects. This pop-up book is pupported with QR code system. Method that used in this system is qualitative. Qualitative datas gained from intenterview, observation, documentation, and from literature review.